2022
DOI: 10.3390/pathogens11050577
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Leukotoxic JP2 Genotype of Aggregatibacter actinomycetemcomitans Is Present in the Population of the West African Island, Sal in Cape Verde: A Pilot Study

Abstract: Aggregatibacter actinomycetemcomitans is strongly associated with severe periodontitis, possibly due to its production of a potent leukotoxin. A genetic variant, the JP2 genotype, was found to produce more leukotoxin than the wild type because of a mutation in the leukotoxin gene, and this genotype is frequently found in African populations. The aim of this study was to investigate whether this JP2 genotype can be found in a randomly selected group of inhabitants of Sal, Cape Verde. Twenty-nine adults between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…In this study, the periodontitis group harbored higher prevalence of Aa non JP2 and JP2 clone both in saliva and diseased sites, whereas they were completely absent at the healthy sites as well as in samples from non-periodontitis subjects. These findings are consistent with those of other studies [ 53 ]. Some studies showed a low Aa detection frequency [ 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the periodontitis group harbored higher prevalence of Aa non JP2 and JP2 clone both in saliva and diseased sites, whereas they were completely absent at the healthy sites as well as in samples from non-periodontitis subjects. These findings are consistent with those of other studies [ 53 ]. Some studies showed a low Aa detection frequency [ 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…The origin of the JP2 genotype was initially suggested to be among individuals living in the Mediterranean part of Africa, and then later on, following a dissemination route through West Africa, and further to North and South America via the transatlantic slave trade [8,9]. Today, there are several reports on the carriage of the JP2 genotype by individuals outside the North and West African regions [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%